ANALISIS KONDISI KEUANGAN TERHADAP PEMBERIAN OPINI AUDIT GOING CONCERN DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERASI - Ario Wibowo, Dandi; Kusuma, Dheni Indra (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This research aims to test the effect of profitability, liquidity, and solvency to the going concern audit opinion, which was conducted on 175 sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This type of study is an associative study that aims to know the effect of profitability, liquidity, and solvency to the going concern audit opinion. KAP reputation as a moderating variable is used by looking at the type of KAP, whether affiliated with Big-4 or not affiliated with Big-4. The type of research data is quantitative, with secondary data obtained from the company's financial statements accessed through the official website of IDX and each sample company. Data processing techniques used are logistic regression analysis methods and moderated regression analysis using IBM SPSS 26. The result of the research indicates that profitability and liquidity have no significant effect on the going concern audit opinion, but solvency has a significant effect with positive direct on the going concern audit opinion. KAP reputation did not moderate this research.